Case Report: Diagnosis and Treatment Esophageal Varices - Risa Ayu Nilmarani; Indra Zachreini; Diana Novita (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Esophageal varices are dilated submucosal veins that connect the portal and systemic circulations to the esophagus. It occurs because of portal hypertension (most caused by cirrhosis), portal blood flow resistance, and increased portal vein blood flow. Esophageal variceal bleeding has a higher morbidity and mortality rate than other upper gastrointestinal bleeding types. In cases of esophageal variceal bleeding, an endoscopic examination is required to make a diagnosis, assess varicose veins, and plan management based on the underlying disease. This case report reviews the diagnosis and management of the esophageal varices at ENT-KL department. Case Presentation: We present a case in which a 54-year-old woman presented to the emergency department of Cut Meutia Hospital with complaints of painful swallowing and a swollen neck. The patient has had this complaint for 5 years, and is getting worse by the day. A barium swallow examination revealed esophageal varices in one-third of the distal esophagus between the seventh and ninth thoracic vertebrae. Conclusion: The patient was diagnosed with esophageal varices and was treated several times before being transferred to a gastroenterology department.